Antimicrobial Residues in Poultry Litter: Assessing the Association of Antimicrobial Persistence with Resistant Escherichia coli Strains - Paula Cortés; Ekaterina Pokrant; Karina Yévenes; Aldo Maddaleno; Andrés Flores; María Belén Vargas; Lina Trincado; Matías Maturana; Lisette Lapierre; Javiera Cornejo (Antibiotics)
Objective: We set out to evaluate the persistence of sulfachloropyridazine, oxytetracycline, and enrofloxacin in broiler chicken litter following therapeutic oral treatment and its association with the isolation of Escherichia coli resistant to these antimicrobials. Methods: Forty broiler chickens were raised under controlled conditions and divided into three experimental groups, each treated with a different antimicrobial, in addition to an untreated/control group. Litter samples were collected post treatment, analyzed by UPLC-MS/MS, and processed for the isolation of E. coli. The antimicrobial susceptibility of E. coli was assessed using the Kirby–Bauer disk diffusion method. Results: Chemical analysis detected concentrations of antimicrobials throughout post treatment, reaching maxima of 42,910.14 μg kg−1, 92,712 μg kg−1, and 9567 μg kg−1 for sulfachloropyridazine, oxytetracycline plus 4-epi-oxytetracycline, and enrofloxacin plus ciprofloxacin, respectively. It was estimated that the concentrations of sulfachloropyridazine, oxytetracycline, and enrofloxacin would persist in broiler litter for 61, 244, and 514 days, respectively. A very strong association was observed between the presence of antimicrobial residues and the antimicrobial resistance of E. coli (p-value < 0.0001, and Cramer’s coefficient of 0.47), and an independence between the level of residue concentration and susceptibility (p-value 0.5262). Conclusions: The persistence of antimicrobial residues contributes to the selection of resistant bacteria, regardless of persistent antimicrobial concentrations. These findings highlight the need for stricter regulations on poultry litter management, including residue thresholds and resistance monitoring, to minimize environmental and public health risks. Proper treatment of poultry litter is essential to ensure its sustainable and safe re-use in agricultural systems.